Interplay of seasonal sunlight, air and leaf temperature in two alpine páramo species, Colombian Andes (2018)
In models of photosynthetic gas exchange, leaf temperature (Tleaf) is often calculated using a combination of derivations of the energy balance equation and measurements of air temperature (Tair). Yet, there are frequently large differences between Tleaf and Tair under natural field conditions, and an energy balance is complicated in complex canopies, especially in tropical ecosystems. In the present study, we aimed to quantify the variation in Tleaf relative to Tair under naturally varying PPFD values in two representative species (Espeletia grandiflora and Chusquea tessellata) of a tropical alpine ecosystem (páramo, Colombian Andes) during both wet and dry seasons. The results of a Structural Equation Model showed that Tleaf was strongly correlated with changes in Tair during both seasons, but large differences (up to 14 °C) occurred between Tair and Tleaf, during the dry season when PPFD varied the most, especially in C. tessellata. Thus, using Tair to proximate Tleaf under variable conditions of incident sunlight could generate substantial errors in estimates of temperature-sensitive physiological processes. These results should be valuable for evaluating the accuracy of carbon and water exchange models within current and future scenarios of climate change in tropical páramos, as well as other ecosystems. © 2018 Elsevier B.V.